The Canopy Structure and Its Impact on Hydrological Performance of Five Local Trees Species Grown in the Purwodadi Botanic Garden - Agung Sri Darmayanti; Abban Putri Fiqa (Journal of Tropical Life Science, 2017)
The hydrological performance of individual tree can be estimated by measuring the stem flow, throughfall and rainfall interception. Water distribution through tree canopy is affected by tree architectural model and another treeâ€™s morphology. This research was done in order to predict the most appropriate tree species that is suitable on soil and water conservation. This research was conducted in Purwodadi Botanic Garden during the rainy season on January 2014 to March 2015, in order to examine the interception rate, throughfall and stemflow on some selected local plants i.e Syzygium polyanthum, Diospyros blancoi, Schleichera oleosa, Madhuca longifolia, and Canarium vulgare. Other observation that support the data, was also measured i.e. Leaf Area Index (LAI), crown depth, leaf size, Diameter of Breast Height (DBH), and height of tree on each species. Results showed that Diospyros blancoi has the highest interception value, which is 53 %, followed by C. vulgare 47.4%, S. oleosa 46.9 %, M. longifolia 38.6%, and S. polyanthum 35.6% respectively. Under the heavy rain, D. blancoi, which has the highest LAI value, also showed the best performance in the rainfall interception value and showed significantly different among others. Canopy interception and stem flow is related to rainfall, the higher the rainfall, the higher the throughfall and the stemflow among species. Morphology on each species, gives the different effect on their partitioning rainfall value. Â  Â